2014
DOI: 10.1109/tdei.2014.004476
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on permeation properties of liquids into HTV silicone rubber materials

Abstract: In this paper, the permeation properties of three types of liquids into HTV silicone rubber with different Alumina Tri-hydrate (ATH) contents had been investigated by weight gain experiments. The influence of differing exposure conditions on the diffusion into silicone rubber, in particular the effect of solution type, solution concentration, and test temperature were explored. Experimental results indicated that the liquids permeation into silicone rubber obeyed anomalous diffusion ways instead of the Fick di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 27 publications
2
45
0
Order By: Relevance
“…After that, discharge of thousands of pC was detected and breakdown happened through the interface between silicone rubber and FRP after few seconds under the applied voltage of 14.2kV. In our previous study, when silicone rubber were immersed in water, weight gain approached saturated condition after 20 days [6]. The water invaded to the interface had influenced the electrical properties of the insulation.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…After that, discharge of thousands of pC was detected and breakdown happened through the interface between silicone rubber and FRP after few seconds under the applied voltage of 14.2kV. In our previous study, when silicone rubber were immersed in water, weight gain approached saturated condition after 20 days [6]. The water invaded to the interface had influenced the electrical properties of the insulation.…”
Section: Resultsmentioning
confidence: 91%
“…On the one hand, the water molecules and ions in the HN03 had the same influence on the insulation with deionized water and NaCI solution. On the other hand, a chemical reaction progress between RN03 and fillers of silicone rubber happened, with holes and cracks on the surface of silicone rubber by SEM [6]. The accumulated acid would cause the deterioration of silane coupling agent and bonding of the interface.…”
Section: E Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is observed from the figure 6a that there is a prominent peak appearing at 1650 cm -1 and 1360 cm -1 (encircled with numbers 1 for 1650 cm -1 and 2 for 1360 cm -1 ). This provides evidence for the introduction of nitric acid to the PDMS [27]. These peaks represent the formation of aluminum nitrites which are introduced because of the reaction of alumina trihydrate with the nitric acid giving rise to the aluminum nitrite nonahydrate [28].…”
Section: Ftir Analysismentioning
confidence: 90%
“…Dehydration of ATH can also suppress the surface erosion induced by dry band arc discharge . Gao et al . studied the water permeation properties of HTV silicone rubber with different ATH contents and concluded that silicone rubber with low ATH content performed better than that with high ATH content.…”
Section: Introductionmentioning
confidence: 99%